Differential use of the Argentine shelf by wintering adults and juveniles southern giant petrels, Macronectes giganteus, from Patagonia - Blanco, Gabriela Silvina; Quintana, Flavio Roberto (Estuarine, Coastal and Shelf Science)
To study habitat use and at-sea movements of southern giant petrels (SGP) during non-breeding period, we deployed 15 satellite transmitters (six adults, nine juveniles) at Isla Arce and Isla Gran Robredo colonies in Patagonia, Argentina. Birds were instrumented during 81.4 ± 37 days. Adult birds used 74% of the Argentine shelf concentrating mainly at the shelf break, middle shelf waters, and the surroundings of the colony. After fledging, juveniles spread to the Argentine, Uruguayan and Brazilian shelves within the South Atlantic. Adults alternated at-sea excursions (12 ± 5 days) with periods at the colony of 3 ± 0.3 days. Contrarily, juveniles moved first to the shelf break and then traveled northwards reaching the south of Brazil. There was some spatial overlap between age classes, but only during the first 30 days after juveniles had fledged; thereafter there was not overlap between the areas used by both age classes. The Argentine shelf is widely used by different species offering a suitable environment for foraging; this may be why adults SGP from Patagonian colonies spend all year-round within the Argentine shelf. The identification of used areas of non-breeding SGP fills a gap in the species knowledge contributing not only to the preservation the species, but also to the management of marine areas globally recognized as important for many other Procellariiformes. Fil: Blanco, Gabriela Silvina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos